2023
DOI: 10.1007/s12652-023-04570-4
|View full text |Cite
|
Sign up to set email alerts
|

A federated learning-enabled predictive analysis to forecast stock market trends

Abstract: This article proposes a federated learning framework to build Random Forest, Support Vector Machine, and Linear Regression models for stock market prediction. The performance of the federated learning is compared against centralised and decentralised learning frameworks to figure out the best fitting approach for stock market prediction. According to the results, federated learning outperforms both centralised and decentralised frameworks in terms of Mean Square Error if Random Forest (MSE = 0.021) and Support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They assert that ML models proved advantageous in the domains of investment decision-making and stock market analysis. Ardakani et al [26] presented a federated learning framework utilizing Random Forest, Support Vector Machine, and Linear Regression models for stock market forecast. To determine the optimal strategy, they contrasted federated learning with centralized and decentralized frameworks, and the strategies of learning frameworks for stock market prediction were elucidated by their results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They assert that ML models proved advantageous in the domains of investment decision-making and stock market analysis. Ardakani et al [26] presented a federated learning framework utilizing Random Forest, Support Vector Machine, and Linear Regression models for stock market forecast. To determine the optimal strategy, they contrasted federated learning with centralized and decentralized frameworks, and the strategies of learning frameworks for stock market prediction were elucidated by their results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning models were beneficial for stock market analysis and investment decisionmaking, according to Tsai et al [18]. Ardakani et al [19] proposed a federated learning framework for stock market prediction using Random Forest, Support Vector Machine, and Linear Regression models. They compared federated learning to centralized and decentralized frameworks to find the best approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Federated learning had a lower model training delay than benchmarks for Linear Regression (9.7 s) and Random Forest (515 s), while decentralized learning saves time for Support Vector Machine (3847 s). Their findings illuminated stock market prediction learning framework strategies [19]. A novel stock price prediction method by Mamluatul et al [20] uses machine learning, stock price data, technical indicators, and Google trends.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This conference paper explores the integration of Long Short-Term Memory (LSTM) and Random Forest algorithms for stock price prediction, showing promising results [5]. In "A federated learningenabled predictive analysis to forecast stock…" [6], The authors suggested machine learning models, such as MLP, to assist investors in making buy-or-sale decisions by fusing big data approaches with fundamental analysis. Cakra practiced the Random Forest and Naive Bayes algorithms to categorize tweets for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%